Influence of natural saferock mineral on soil micro-bilogical parameters under rice-wheat cropping system - Ranva, Santosh; Singh, YV; Jain, Neelam; Bajiya, Deva Ram (Bangladesh Journal of Botany, 2019)
A field experiment was conducted to study the effect of SafeRock Minerals (SRM) application on soil microbiological parameters in rice-wheat cropping system. The experiments consisted of two methods of rice and wheat establishment and six different levels of crop nutrition including SRM with mineral fertilizers and organic manure (FYM). The rice was grown in kharif (June to October) season through aerobic direct seeded condition and flooded transplanted system. During rabi (October to April) season wheat was cultivated by two establishment methods viz. system of wheat intensification (SWI) and conventional wheat. The high yielding varieties of Basmati rice (Pusa Basmati 1509) and wheat (HD 2967) were used in the experiment. The results revealed that the soils of rice and wheat crops showed significant improvement in available N, P and K and soil microbial parameters (enzymatic activities and microbial biomass carbon) due to the integrated application of 250 kg/ha SRM + 100% recommended dose of fertilizer (RDF) and 250 kg/ha SRM + 50% RDF (chemical) + 25% RDF (organic) and 250 kg/ha SRM + 50% organic-FYM (10.0 t/ha) over the sole SRM application under both the methods of stand establishment of rice as well as wheat.